Immune Thrombocytopenic Purpura Secondary to Cytomegalovirus Infection: A Case Report - Flores-Chang, Bessy S.; Arias-Morales, Carlos E.; Wadskier, Francis G.; Gupta, Sorab; Stoicea, Nicoleta (Frontiers in Medicine, 2015)
Immune Thrombocytopenic Purpura (ITP) is defined as an acquired thrombocytopenia with antibodies detected against platelet surface antigens, and it is the most common form of thrombocytopenia in otherwise asymptomatic adults. ITP secondary to an underlying condition is a diagnosis of exclusion that is essential to establish for treatment efficacy. Secondary thrombocytopenia caused by Cytomegalovirus (CMV) is common, however case reports associated with diagnosis in immunocompetent adults are rare, and to the best of our knowledge only 20 publications have been associated with this diagnosis. Our report is based on a clinical presentation of a 37 year old female complaining of petechiae, heavy menses, shortness of breath and a platelet count of 1 X 109 /L. Treatment with IVIG and steroids failed to improve platelet count. Subsequently, an infectious laboratory workup was performed, detecting CMV infection, and treatment with antiviral agents was initiated, causing platelet count to increase as viral load decreased.